A Consideration of the Seven Sins of Memory in the Context of Creative Cognition. Issue 4 (2nd October 2018) - Ditta, Annie S.; Storm, Benjamin C.
Abstract : Schacter's (2001) work on The Seven Sins of Memory conceptualized and communicated many of the failures of memory and their critical role in cognition. At the heart of the framework is the idea that memory often fails not because it is dysfunctional or maladaptive, but because it prioritizes flexibility and the ability to think and behave adaptively over the ability to retain and remember veraciously. This article adapts the 7 sins framework to a new domain—that of creative cognition. Each of the 7 sins are discussed in relation to how they might play a role in allowing people to generate new ideas, solve problems, and overcome the various barriers that hinder creative thought. Expanding upon the creative cognition approach, it is argued that memory and creativity are intrinsically interconnected and that one's ability to think and behave creatively relies in part on the ability to forget and misremember.